Bi-lamellar lower eyelid reconstruction with superficial temporal artery island flap and hard palate muco-periosteal free graft - Jacob, V; Mokal, N J; Deshpande, S N (Indian Journal of Plastic Surgery, 2005)
Three cases of single stage, bi-lamellar reconstruction of full-thickness, horizontal, lateral three-quarter lower eyelid defects using pedicled island flaps of adjacent vascular territories and hard palate muco-periosteal graft are being presented. All cases were done for Basal Cell Carcinoma of the region. While the island flaps allowed for a simple, single stage reconstruction of the external lamella, the hard palate muco-periosteal graft, by virtue of its inherent resilience and a rich glandular component, took well and provided for a good functional and aesthetic result.The follow-up ranged from 6 to 40 months and the final result has been oncologically, functionally and aesthetically satisfactory.
Keywords: Island superficial temporal artery flap; Hard palatal muco-periosteal graft; Bi-lamellar lower eyelid defect reconstruction; Full thickness lower eyelid defect reconstruction